Haiti : Second and Third Reviews Under the Extended Credit Facility: Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report, 2012)
The staff report on Haiti's second and third reviews under the Extended Credit Facility is examined. Haiti has emerged from a protracted and tumultuous electoral period. The reconstruction is under way, albeit at a slower pace than anticipated, owing mainly to the protracted electoral agenda and Haiti's limited administrative and absorptive capacity. The damage caused by the earthquake has been massive, estimated at the equivalent to 120 percent of GDP. The authorities need to sustain high growth, alleviate poverty, and strengthen the country's resilience to external shocks.